Natural resources and conflict in Sudan : addressing environmental issues in a post-conflict situation : the case of Afghanistan - Caas, Francois Henri (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.